helppppp ASAP
WILL MARK BRAINLIEST!!!!!!!!!!
![helppppp ASAP WILL MARK BRAINLIEST class=](https://us-static.z-dn.net/files/dfb/bb7f671c0a7b5b16f1f5de84f958c6e8.png)
Answer:
[tex]m\angle GKH=m\angle JKI[/tex] Subtraction Property
Step-by-step explanation:
We are given that line GI intersects line JH at point K. The proof of [tex]m\angle GKH\cong m\angle JKI[/tex] is shown.
To complete the 5th statement in the proof.
Solution:
To prove ∠GKH ≅ ∠JKI , we need to first show that [tex]m\angle GKH=m\angle JKI[/tex]
From the 4th statement given we can use the properties of equality.
4th Step is as follows :
[tex]m\angle GKH+m\angle HKI=m\angle JKI+m\angle HKI[/tex]
Using subtraction property: [If [tex]a+b=c+b[/tex] , then [tex]a=c[/tex]]
Subtracting both sides by m∠HKI
[tex]m\angle GKH+m\angle HKI-m\angle HKI=m\angle JKI+m\angle HKI-m\angle HKI[/tex]
Thus, we have the 5th step as:
[tex]m\angle GKH=m\angle JKI[/tex]